Implementation of Electronic Worksheets Based on Problem-based Learning on Acid-Base Materials to Develop Students’ Problem-solving Ability - Putri Deti Ratih; Eli Rohaeti (Postgraduate, University of Mataram, 2022)
Learning during a pandemic requires teachers to innovate in developing teaching materials that can be used in online learning. The use of problem-based learning-based electronic student worksheets (SW) can be an innovative solution for teaching materials that are integrated with technological developments that can help the online learning process. This study aims to analyze the differences in students' problem-solving abilities between classes that use problem-based learning-based electronic student worksheets and classes that do not use problem-based learning-based electronic student worksheets on acid-base materials and analyze the effective contribution of the application of problem-based electronic worksheets. -based learning on students' problem-solving abilities on acid-base material. This research is a Quasi Experiment research type with post-test only control-group type. The research instruments used are syllabus, lesson plans, problem-based learning-based electronic worksheets and problem-solving skills. The data analysis technique in this study consisted of 2 analyzes, namely the independent sample t-test and effect size analysis. The results of the development research show that: (1) there are differences in the problem-solving abilities of students between classes that use problem-based learning-based electronic student worksheets and those that do not use problem-based learning-based electronic student worksheets on acid-base materials for class XI MIPA, (2) Problem-based learning-based electronic worksheets provide an effective contribution to students' problem-solving abilities on acid-base materials with a percentage of 2.5%.